PENERAPAN IoT PADA SISTEM PENGONTROL LAMPU MENGGUNAKAN NODEMCU ESP8266 - Jabal Nur; Astina Sahrani (Prodi Teknik Informatika Unidayan Baubau, 2022)
The application of the Internet of Things (IoT) to electronic equipment is becoming more important to facilitate activities. The convenience of carrying out daily activities at home is more helpful if it can be done remotely. With the existence of IoT technology, the problem of turning off the house lights will be helped by a system that is controlled remotely using the internet network. This study aims to make a prototype of a remote light control device using the NodeMCU ESP8266 and utilize the blink application with IoT technology. This research produced a remote light controller prototype that can be controlled using an internet network, so that it can control lights easily and can avoid wasting electricity due to lights that have been forgotten to turn off.